Clinician Compliance With DVLA Guidelines in a Female Acute Inpatient Unit: Evaluating Documentation and Advice on Driving Status - Alka Adhikari; Noemi Stockdale (BJPsych Open)
Aims: The aim of this study was to assess clinician compliance with DVLA guidelines regarding driving status and advice for patients in an acute female inpatient unit. Specifically, the study sought to identify the documentation of driving status in patient records, the provision of DVLA-compliant advice, and the effectiveness of implemented recommendations.